(untitled) (Journal of Economic Research & Business Administration, 2016)
The paper presents a comprehensive analysis of the state and consider ways, factors, measures and mechanisms for the health protection devel opment and physical development of the population in biosphere crisis. Identified the problems encountered in the implementation of radical eco nomic reforms and modernization of health care in Kazakhstan. Reviews the measures, including the scientific, organizational and methodological steps to resolve the obstacles to rapid development of public health.